Effects of silane surface treatment of cellulose nanocrystals on the tensile properties of cellulose-polyvinyl chloride nanocomposite - Rasha M. Sheltami,; Hanieh Kargarzadeh,; Ibrahim Abdullah, (Universiti Kebangsaan Malaysia, 2015)
Cellulose nanocrystals (CNC) from mengkuang leaves (Pandanus tectorius) were investigated as potential reinforcement in poly(vinyl chloride) (PVC) matrix. The surface of CNC was modified with silane coupling agent to improve filler-matrix adhesion. Solution casting method was used to prepare PVC nanocomposites with various amounts of modified (SCNC) and unmodified (CNC) nanocrystals. Both SCNC and CNC were examined by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD) which showed that surface chemical modification has occurred. An increase in tensile strength was observed with the addition of SCNC compared to the CNC. However, the elongation at break of the nanocomposites was found to decrease with the increase of both fillers loading. An increasing trend was observed in the tensile modulus with the addition of CNC to the PVC matrix, but decreasing with the addition of SCNC. The morphology of a fractured surface of nanocomposites showed silane modification reduced the number of voids in the structure of PVC. The observation indicated the adhesion between the fiber and the matrix had improved upon surface modification of the nanocrystals with silane.